Dispersant‐free dyeing of poly(lactic acid) fabric with temporarily solubilised disperse dyes from azopyridone derivatives. (30th June 2016) - Park, Young Ki; Jo, A Ra; Jang, Seung Soon; Lee, Jung Jin
Abstract : Poly(lactic acid) fibre is derived from annually renewable crops and known to be 100% compostable. In order to extend its environmental friendliness into the dyeing process, dispersant‐free dyeing of poly(lactic acid) fabric with three temporarily solubilised azo disperse dyes based on hydroxypyridone moiety containing a β‐sulphatoethylsulphonyl group was investigated. The dyes were successfully applied to poly(lactic acid) fabric without the use of dispersants. The colour yields of the dyes on poly(lactic acid) fabric were observed to be dependent on dyebath pH and dyeing temperature. The optimum results were obtained at pH 4–5 and 110 °C. One of the dyes showed a colour yield as good as that of a commercial disperse dye and good build‐up on poly(lactic acid) fabric. All of the dyes could be alkali cleared owing to ionisation of the dye under mild alkaline conditions. Wash fastness was good to very good, and light fastness was good. The chemical oxygen demand levels of the poly(lactic acid) dyeing effluent from the dyes were considerably lower than those from a commercial disperse dye.